2015
DOI: 10.1021/acs.est.5b00399
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Natural Estrogens and Their Conjugates in Municipal Wastewater Treatment Plants: A Critical Review

Abstract: This article reviews studies focusing on the removal performance of natural estrogens in municipal wastewater treatment plants (WWTPs). Key factors influencing removal include: sludge retention time (SRT), aeration, temperature, mixed liquor suspended solids (MLSS), and substrate concentration. Batch studies show that natural estrogens should biodegrade well; however, batch observations do not always agree with observations from full-scale municipal WWTPs. To explain this discrepancy, deconjugation kinetics of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
67
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(77 citation statements)
references
References 93 publications
7
67
0
2
Order By: Relevance
“…10 As a result, an underestimation of removal efficiency will inevitably occur if the conjugated forms occupy a considerable portion of the total estrogens. 8 This necessitates the detection of conjugated estrogens in WWTPs when investigating the behavior and fate of EDCs.…”
Section: 9mentioning
confidence: 99%
“…10 As a result, an underestimation of removal efficiency will inevitably occur if the conjugated forms occupy a considerable portion of the total estrogens. 8 This necessitates the detection of conjugated estrogens in WWTPs when investigating the behavior and fate of EDCs.…”
Section: 9mentioning
confidence: 99%
“…An important reason for the inconsistencies is that the operational parameters, including temperature, hydraulic retention time (HRT) and sludge retention time (SRT), varied greatly among the different studies. However, studies that discussed the influence of operational parameters on the NE removal also showed significant discrepancies (Clara et al, 2005;Hashimoto et al, 2007;Liu et al, 2015;Nakada et al, 2006). It is particularly difficult to isolate the influence of one operational parameter, as the treatment processes and other operational parameters differed across these studies.…”
Section: Introductionmentioning
confidence: 99%
“…Among the EDCs, natural estrogens (NEs), including estrone (E1), 17 b-estradiol (E2) and estriol (E3), were the most studied because of their strong estrogenic potencies (Liu et al, 2015). Human and animal excretions constituted the main sources of NEs in the environment, while the occurrence of NEs in municipal wastewater is primarily attributed to human excretions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Suspended pollutants in urban sewage are characterized by their slow biodegradation (Jordao et al, 2002;Liu et al, 2015;Munoz et al, 2009). However, a few issues need to be resolved before adapting microbes for implementation in high suspended solids (SS) urban sewage treatment plants.…”
Section: Introductionmentioning
confidence: 99%